Promotion of colorectal cancer by transcription factor BHLHE40 involves upregulation of ADAM19 and KLF7 - Sui, Yuan; Jiang, Hanlin; Kellogg, Collyn M.; Oh, Sangphil; Janknecht, Ralf (Frontiers in Oncology, 2023)
BHLHE40 is a transcription factor, whose role in colorectal cancer has remained elusive. We demonstrate that the BHLHE40 gene is upregulated in colorectal tumors. Transcription of BHLHE40 was jointly stimulated by the DNA-binding ETV1 protein and two associated histone demethylases, JMJD1A/KDM3A and JMJD2A/KDM4A, which were shown to also form complexes on their own and whose enzymatic activity was required for BHLHE40 upregulation. Chromatin immunoprecipitation assays revealed that ETV1, JMJD1A and JMJD2A interacted with several regions within the BHLHE40 gene promoter, suggesting that these three factors directly control BHLHE40 transcription. BHLHE40 downregulation suppressed both growth and clonogenic activity of human HCT116 colorectal cancer cells, strongly hinting at a pro-tumorigenic role of BHLHE40. Through RNA sequencing, the transcription factor KLF7 and the metalloproteinase ADAM19 were identified as putative BHLHE40 downstream effectors. Bioinformatic analyses showed that both KLF7 and ADAM19 are upregulated in colorectal tumors as well as associated with worse survival and their downregulation impaired HCT116 clonogenic activity. In addition, ADAM19, but not KLF7, downregulation reduced HCT116 cell growth. Overall, these data have revealed a ETV1/JMJD1A/JMJD2ABHLHE40 axis that may stimulate colorectal tumorigenesis through upregulation of genes such as KLF7 and ADAM19, suggesting that targeting this axis represents a potential novel therapeutic avenue.